Synthesis, Characterization Of 1,3-Diarylpropenes And Tricyclic Indolines And The Cytotoxic Activities Of 1,3-Diarylpropenes - Tan, Aik Sian (2022)
Alkaloids are crucial nitrogen-containing compounds that exhibit diverse biological and pharmaceutical activity, regardless of the compound scaffold. Accordingly, it drives the synthesis of amido 1,3-diarylpropene and 6-5-4 tricyclic indoline under the alkaloid class, potentially the chemotherapeutic agents for cancer treatment. In the first study, forty (40) 1,3-diarylpropene derivatives, designed analogs of stilbenoids and dihydrostilbenoids, were synthesized by the palladiumcatalyzed reactions of 2-amidoiodobenzene derivatives with either estragole or eugenol.